Amiodarone is associated with adverse outcomes in patients with sustained ventricular arrhythmias upgraded to cardiac resynchronization therapy—defibrillators. (4th January 2019) - Adelstein, Evan C.; Althouse, Andrew D.; Davis, Lydia; Schwartzman, David; Bazaz, Raveen; Jain, Sandeep; Wang, Norman; Saba, Samir
Abstract: Introduction: Amiodarone reduces recurrent ventricular tachyarrhythmias (VTA) but may worsen cardiovascular outcomes in heart failure (HF) patients. Cardiac resynchronization therapy (CRT) may also be antiarrhythmic. When patients with prior sustained VTA are upgraded to CRT defibrillators (CRT‐D) from conventional implantable cardioverter‐defibrillators (ICDs), should concomitant amiodarone be continued or is CRT's antiarrhythmic potential sufficient? Methods and Results: We identified 67 patients from a prospective CRT registry with spontaneous sustained VTA, New York Heart Association (NYHA) II‐IV HF, and left bundle‐branch block (LBBB) who were upgraded to CRT defibrillators from conventional ICDs. We compared changes in QRS duration and left ventricular ejection fraction (LVEF) pre‐ and post‐CRT, time to death, transplant or ventricular assist device (VAD), and time to recurrent VTA therapies between 37 patients continuing amiodarone therapy and 30 amiodarone‐naïve patients. Amiodarone‐treated patients had worse renal function and a higher prevalence of prior VTA storm compared with amiodarone‐naïve patients. After CRT, amiodarone‐treated patients demonstrated less QRS narrowing (8 vs 20 ms; P = 0.021) and less LVEF improvement (−2.7 vs +5.2%; P = 0.006). Over 29 months, 31 (47%) patients died and 13 (20%) received transplant or VAD. Risk of death, transplant, or VAD was greater in amiodarone‐treated than ‐naïve patients (corrected hazard ratio [HR], 2.14; 95% confidence interval [CI], 1.12‐4.11; P = 0.022). Appropriate CRT‐D therapies occurred in 37 (55%) patients; amiodarone use was not associated time to first therapy (HR, 1.13; 95% CI, 0.59‐2.16; P = 0.72). Conclusion: In patients with sustained VTA and LBBB upgraded from conventional ICDs to CRT defibrillators, concomitant amiodarone use is associated with less QRS narrowing, less LVEF improvement, greater risk of death, transplant, or VAD, and similar risk of recurrent VTA.